2019
DOI: 10.1371/journal.pgen.1008062
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction disrupts stem cell homeostasis in testes of aged male Drosophila via an induced microenvironment

Abstract: Stem cells rely on instructive cues from their environment. Alterations in microenvironments might contribute to tissue dysfunction and disease pathogenesis. Germline stem cells (GSCs) and cyst stem cells (CySC) in Drosophila testes are normally maintained in the apical area by the testicular hub. In this study, we found that reproduction leads to accumulation of early differentiating daughters of CySCs and GSCs in the testes of aged male flies, due to hyperactivation of Jun-N-terminal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 117 publications
1
41
0
Order By: Relevance
“…Previously we have shown that reproduction increases Egr levels in the testicular muscle to hyperactivate JNK signaling in somatic cyst cells 12 . Since JNK signaling is also activated in cyst cells in response to amino acid starvation 3 , we then asked if protein starvation induces Egr protein upregulation in testicular smooth muscles.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Previously we have shown that reproduction increases Egr levels in the testicular muscle to hyperactivate JNK signaling in somatic cyst cells 12 . Since JNK signaling is also activated in cyst cells in response to amino acid starvation 3 , we then asked if protein starvation induces Egr protein upregulation in testicular smooth muscles.…”
Section: Resultsmentioning
confidence: 96%
“…We found that Egr is required for the fast recovery of CySCs induced by protein resupply. CySCs are defined as the Zfh-1 positive cells immediately adjacent to GSCs 12 , 27 . In wild-type Oregon-R ( OR ) flies, the number of CySC increased dramatically from 11 to 22 during the first two days of refeeding (R1 and R2) (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations